Lafadz yang Bermakna Kekejian dalam Perspektif Al-Qur’an - Fauzi, Muhammad Haris (MAGHZA, 2020)
This paper discusses the qurâ€™anic concept about an atrocity that imagined in lafadz fahsyÄâ€™, in which in the view of some people, the atrocity still confused in definition and understanding with some closest lafadzs, and frequency caused the confusion in definition and misleading of concepts. Al-Qurâ€™an still guides the people not to be trapped in atrocity behavior for themselves and their circles. Al-Qurâ€™an uses the lafadz fahsyÄâ€™to refer to all shapes of action, expression, and mind that pass the border of a corridor in syariat. But on another side, al-Qurâ€™an also uses the lafadz fÄhisyah, fawÄhisy, zina, khabis, munkar, or some closest lafadzs to refers to all action pass the limit, and this is seen as contradictive and ambiguous. With the semantic method, the writer concluded that lafadz fahsyÄâ€™or atrocity when analyzing with comprehensively except refer to the meaning doing something contrary with norm society, but also refer to unwilling attitude to pay the tithe, defame other people with destructive information, doing Zina and get the forbidden thing or leave the halal substance in one case.